Selected methods of utilisations used tires - Wojciechowski, A.; Michalski, R.; Kamińska, E. (Polimery, 2012)
The management of an increasing mass of the stored waste tyres, which pose a risk to the environment, has become a serious problem. The paper is an attempt to assess the current state of the management and recycling of tyres from the legal, economic and technological points of view. The examples of uses of the products of material recycling and the environmental benefits arising from the recovery of energy were presented.